Chemical compositions, extraction technology, and antioxidant activity of petroleum ether extract from Abutilon theophrasti Medic. leaves. Issue 1 (1st January 2018) - Tian, Chunlian; Gao, Xiang; Yang, Jie; Guo, Yuru; Wang, Hong; Liu, Mingchun
ABSTRACT: Petroleum ether extract from Abutilon theophrasti Medic. leaves was optimized by response surface methodology, and the optimal extraction conditions were as follows: ratio of solvent to material (20.12 mL/g), extraction time (5.45 h), and Soxhlet extraction temperature (61.32°C). And the yield of petroleum ether extract collected in August, September, and October was (2.05 ± 0.02)%, (2.39 ± 0.01)%, and (2.32 ± 0.02)%, respectively. The September and October extracts exhibited a better antioxidant activity, which was proved by DPPH·scavenging ability (IC50 value of 327.5 and 331.5 μg/mL), ABTS ·+ scavenging ability (IC50 value of 170.1 and 182.1 μg/mL), and reducing power (0.31 and 0.28 mmol Fe 2+ /100 μg/mL). Meanwhile, the gas chromatograph-mass spectrometry analysis revealed that the main antioxidant components contained 9, 12, 15-octadecatrienoic acid and 9, 12, 15-octadecatrienoic acid, ethyl ester (Z, Z, Z) in three petroleum ether extracts. Therefore, petroleum ether extract from Abutilon theophrasti Medic. leaves can be a potential resource of natural antioxidants in pharmaceutical, medicine, food, and chemical industries.